Pengaruh Lingkungan Kerja, Penempatan Kerja dan Beban Kerja terhadap Kepuasan Kerja Operator Gardu Induk pada PT PLN (Persero) Unit Pelaksana Transmisi Banda Aceh Provinsi Aceh - Rahmat Adriansyah; Lukman T. Ibrahim; Cut Delsie Hasrina (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to determine how the influence of work environment, work placement and workload on job satisfaction of substation operators at PT. PLN (Persero) Unit of Aceh province. The data analysis technique used is multiple linear regression. Based on the results of this study shows that partially and simultaneously have an effect on job satisfaction of substation operators. Then in this study obtained multiple linear regression equation which can be interpreted that a constant value of 6,878 shows a positive value if the variables of work environment, work placement and workload are considered constant or equal to zero, then the job satisfaction of substation operators at PT. PLN (Persero) Unit of Banda Aceh province of Aceh was 6,878. Then for the work environment variable (X1) produces a regression coefficient of 0.646 (65%) and a positive sign, the value means that if the work environment variable increases, it will also increase the job satisfaction variable by 65%. For the job placement variable produces a regression coefficient of 0.401 (40%) and a positive sign, the value means that if the job placement variable increases, it will also increase the job satisfaction variable by 40%. While the workload variable produces a regression coefficient of -0.208 (21%) and is marked negative, the value means that if the workload variable decreases, it will increase the job satisfaction variable by 21% and vice versa